Enhancer-directed gene delivery for digit regeneration based on conserved epidermal factors - David A. Brown; Katja K. Koll; Erin Brush; Grant Darner; Timothy Curtis; Thomas Dvergsten; Melissa Tran; Colleen Milligan; David W. Wolfson; Trevor J. Gonzalez; Sydney Jeffs; Alyssa Ehrhardt; et al. (Proceedings of the National Academy of Sciences, 2026)
Limb loss remains a significant clinical challenge, but regenerative medicine approaches such as gene therapy offer a promising strategy to trigger endogenous regeneration programs. Optimal vector configurations and molecular targets for appendicular skeletal repair are not well defined. Here, we leveraged insights from species with a high endogenous capacity for appendage regeneration to design an enhancer-directed gene delivery platform that functions during mouse digit regeneration, a well-characterized model for partial limb regeneration in mammals. Single-cell RNA sequencing of zebrafish caudal fin regeneration, combined with expression data in regenerating salamander limbs and mouse digit tips, implicated the SP family of transcription factors as conserved, epidermally expressed mediators of appendage regrowth. Null mutants of Sp8 demonstrated impaired limb regeneration in salamanders, while conditional knockout of Sp6 and/or Sp8 in the mouse basal epidermis resulted in defective bony digit tip regeneration, involving an IL-17-mediated osteoclastogenic program. Spatiotemporally focused expression of FGF8, a known target of SP factors, using a zebrafish-derived tissue regeneration enhancer element via adeno-associated viral vectors, could partially rescue digit tip regeneration in SP knockout mice and accelerate digit regeneration in wild-type mice. Our results demonstrate a contextual gene therapy approach to address limb loss based on genes like SP transcription factors conserved across multiple contexts of appendage regeneration.